Discovery of new mutually orthogonal bioorthogonal cycloaddition pairs through computational screening. Issue 2 (19th November 2015) - Narayanam, Maruthi Kumar; Liang, Yong; Houk, K. N.; Murphy, Jennifer M.
Abstract : The sydnone-dibenzocyclooctyne and norbornene-tetrazine cycloadditions are both bioorthogonal and mutually orthogonal, used for simultaneous labeling of two targets. Abstract : Density functional theory (DFT) calculations and experiments in tandem led to discoveries of new reactivities and selectivities involving bioorthogonal sydnone cycloadditions. Dibenzocyclooctyne derivatives (DIBAC and BARAC) were identified to be especially reactive dipolarophiles, which undergo the (3 + 2) cycloadditions with N -phenyl sydnone with the rate constant of up to 1.46 M −1 s −1 . Most significantly, the sydnone-dibenzocyclooctyne and norbornene-tetrazine cycloadditions were predicted to be mutually orthogonal. This was validated experimentally and used for highly selective fluorescence labeling of two proteins simultaneously.